2016
DOI: 10.15287/afr.2016.572
|View full text |Cite
|
Sign up to set email alerts
|

Seedling regeneration on decayed pine logs after the deforestation events caused by pine wilt disease

Abstract: Fukasawa Y., 2016. Seedling regeneration on decayed pine logs after the deforestation events caused by pine wilt disease. Ann. For. Abstract. Coarse woody debris (CWD) forms an important habitat suitable for tree seedling establishment, and the CWD decay process influences tree seedling community. In Japan, a severe dieback of Pinus densiflora Sieb. & Zucc. caused by pine wilt disease (PWD) damaged huge areas of pine stands but creates huge mass of pine CWD. It is important to know the factors influencing see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It has previously been reported that seedlings of Picea abies and P. jezoensis preferentially regenerate on logs that are dominated by white-rot fungi rather than brown-rot fungi (Bacˇe et al 2012;Ando et al 2017). Similarly, seedlings of Pinus densiflora are less likely to occur on brown-rotted logs (Fukasawa 2016) and exhibit faster growth on white-rotted logs than on soil (Fukasawa 2015). However, seedlings of Clethra barbinervis (Fukasawa 2012), Toxicodendron trichocarpum (also referred to as Rhus trichocarpa; Fukasawa 2016), and Cryptomeria japonica (Fukasawa and Komagata 2017; show the reverse trend, preferentially regenerating on brown-rotted logs over other the decay types.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has previously been reported that seedlings of Picea abies and P. jezoensis preferentially regenerate on logs that are dominated by white-rot fungi rather than brown-rot fungi (Bacˇe et al 2012;Ando et al 2017). Similarly, seedlings of Pinus densiflora are less likely to occur on brown-rotted logs (Fukasawa 2016) and exhibit faster growth on white-rotted logs than on soil (Fukasawa 2015). However, seedlings of Clethra barbinervis (Fukasawa 2012), Toxicodendron trichocarpum (also referred to as Rhus trichocarpa; Fukasawa 2016), and Cryptomeria japonica (Fukasawa and Komagata 2017; show the reverse trend, preferentially regenerating on brown-rotted logs over other the decay types.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, CWD also plays an important role in forest recovery, as it functions as a seedbed for trees, particularly conifers in the genera Abies (Narukawa et al 2003), Picea (Ando et al 2017), Thuja (Scott and Murphy 1987), and Tsuga (Harmon and Franklin 1989). It has also been reported that the conifers Chamaecyparis obtusa and Cryptomeria japonica regenerate on CWD in rural forests in Japan (Yamamoto 1993;Ota et al 2012;Fukasawa 2016;Fukasawa and Komagata 2017;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors such as CWD size (diameter, Takahashi 1994), bryophyte cover (Nakamura 1992;Iijima and Shibuya 2010), and wood decay class ) influence seedling colonization. In addition to these factors, recent studies reported that wood decay type is also a strong driver of seedling colonization (Bacˇe et al 2012;Fukasawa 2012;Fukasawa et al 2015;Fukasawa 2016).…”
Section: Introductionmentioning
confidence: 99%